Multiplicity of 2-nodal solutions of the Yamabe equation - Ortiz, Jorge Dávila; González, Héctor Barrantes; Lima, Isidro H. Munive (Topological Methods in Nonlinear Analysis, 2024)
Given a closed Riemannian manifold $(M,g)$, we use the gradient flow method and Sign-Changing Critical Point Theory toprove multiplicity results for $2$-nodal solutions of a subcritical non-linear equation on $(M,g)$, see \eqref{yam-nodal-1} below. If $(N,h)$ is a closed Riemannian manifold of constant positive scalar curvature our result gives multiplicity results for the Yamabe-type equation on theRiemannian product $(M× N , g + \ve h )$, for $\ve > 0$ small.